(untitled) (African Human Mobility Review, 2021)
Using the experiences of Ghanaian and Nigerian migrants who were implicated in the 2011 Libyan crisis as a case study, this paper highlights the importance of examining micro-level factors in explaining migration decision-making processes. It therefore challenges the uncritical use of macro-level factors as exogenous ‘root causes’ of migration especially in developing country contexts. Adopting mainly qualitative approaches among seventy-five key informants from six distinct categories, the study finds that migration culture, household livelihood aspirations, geographical propinquity, the existence of social networks and migrant smuggling rings motivate migrations to Libya. The paper also challenges scholarship on the 2011 Libyan crisis that treats the experiences of sub-Saharan African (SSA) migrants in the country as an undifferentiated group. The paper concludes that within a developing country context, the political economy of the origin country contributes to the establishment, over time, of a migration culture especially among youth who feel trapped in ‘waithood’ and are unable to realize basic socio-cultural and economic markers in life. The paper recommends the regionalization of evacuation and repatriation programmes to facilitate the timely extraction of trapped migrants from countries in crisis.